ECOTOURISM DIGITALIZATION: IMPLEMENTASI APLIKASI PENGELOLAAN TIKET PADA EKOWISATA PANTAI PANCER - Eka Bambang Gusminto; Didik Pudjo Musmedi; Tria Putri Noviasari; Vanya Pinkan Maridelana; Batara Aulia Kadafi; Salsabilah Amalia Putri (LPPM Universitas Bina Bangsa, 2024)
The tourism sector is a very effective sector for improving the regional economy in Indonesia. The implementation of digital information technology has a positive impact on the tourism sector, thereby enabling a tourism revolution in the present and future. Operational activities related to ticket sales in the Pancer Beach ecotourism area are still carried out manually and have yet to be computed, which causes financial reporting to be less effective and efficient. Thus, it is necessary to integrate digital technology by developing a web-based ticket management information system to make the transaction recording process more efficient and increase the transparency of financial reports. The Pancer Beach ticket application was built using the waterfall method, which consists of 5 stages: software requirements analysis, application design, code generation, application testing, and support. The results show that the Pancer Beach ticket application system was built based on the needs and capacity of the Pancer Beach ecotourism area staff. Features available in the application include the Dashboard menu, Settings and information, Tickets, and Income Reports. The integration of digital technology in the Pancer Beach ticket application makes operational services for visitors, especially those related to ticket management, faster, more efficient, and transparent